Dermatology clinical case - Ferreira,Adriana (2021)
Abstract Lyme disease is a spirochaetal infection caused by Borrelia Burgdorferi sensu lato, which is transmitted by infected ticks of the genus Ixodes. It has a broad spectrum of clinical manifestations which, associated with its low incidence in Portugal, requires a high level of clinical suspicion for diagnosis. However, it is considered endemic in certain geographic areas, like Central Europe. The authors report the case of a child, living in Switzerland, who developed multiple erythema migrans lesions. Although parents did not recall a history of tick bite, Lyme disease diagnosis was established on clinical grounds, based on erythema and epidemiologic findings. When properly treated with oral antibiotic therapy, Lyme disease has an excellent prognosis. This case highlights the importance of epidemiologic history as a diagnostic clue.